All-in-one CRISPR/Cas-engineered glucocorticoid-receptor knock-out EBV-gp350-CAR knock-in T cells are potent and resistant to dexamethasone - Theresa Kaeuferle; Maximilian Zwermann; Nadine Stoll; Paulina Ferrada-Ernst; Lena Jablonowski; Reinhard Zeidler; Semjon Willier; Dana Stenger; Abdallah Yassin; Renata Stripecke; Tobias Feuchtinger (Experimental Hematology & Oncology, 2025)
Abstract Background Epstein-Barr virus (EBV) reactivation in immunocompromised patients and post-transplantation is associated with morbidity, mortality and with the onset of a variety of malignant diseases. Adoptive T-cell therapies have emerged as promising therapeutic options, but post-transplant immunosuppression jeopardizes the protective anti-EBV immune surveillance by adoptively transferred T cells. Methods Using an all-in-one CRISPR/Cas-mediated approach, we inserted an anti-EBV (gp350) CAR into the T-cell receptor (TRAC) locus and simultaneously knocked-out the glucocorticoid receptor (GR) on a good manufacturing practice (GMP)-compatible platform. Results CAR knock-in (CARKI) was confirmed in primary human T cells on genetic and on protein level with a mean efficiency of 41%. With 83%, additional GR knock-out was highly efficient in CARKI cells. On a functional level CARKIGRKO T cells showed target-specific potency in terms of cytokine secretion patterns, proliferative capacity and cytotoxic activity against gp350-expressing target cells. Further, CARKIGRKO T cells were insensitive to dexamethasone treatment and maintained T-cell functionality. In contrast, CARKIGRKO T cells were sensitive to the GR-independent immunosuppressant cyclosporine A (CsA), thereby providing a rescue treatment for patients in case of safety issues. Conclusions The study lays the proof-of-concept for virus-free all-in-one GMP-manufacturing of glucocorticoid-resistant CAR T-cell products. Further, the glucocorticoid-resistant gp350-CAR T cells can provide a future therapeutic option for high-risk post-transplant patients with EBV-reactivations or patients with EBV-associated pathologies requiring steroid treatment.